Microbial Entomopathogens In Control Of Mosquito Borne Diseases - ARUNAVA KALI, (International Journal of Pharma and Bio Sciences, 2015)
Mosquito is the most significant vector in medical entomology. Various species of mosquitoes are implicated in the transmission of a wide variety of human and animal diseases. With the widespread use of chemical insecticides to reduce the burden of mosquito-borne diseases, there is increasing concern of environmental adulteration and its deleterious effects on human health. Consequently, biological methods have gained more importance. Several novel biological control measures are in the process of development. This review provides a brief update of new and existing methods of mosquito control using entomopathogenic microbes.